A Study to Assess the Combined Effectiveness of Kinesio Taping and A Corrective Footwear for the Ward Nurses with Foot Pain: Life Sciences-Physiotherapy - Gurung, Nirpana; Dutta, Abhijit; Bhattacharyya, Shalaka; Kalita, Abhijit (International Journal of Life Science and Pharma Research, 2023)
Foot pain is an abnormal pain and discomfort in one or more parts of the foot, like heels, arches, and soles. Minor injuries to the foot, repetitive stress or overuse, and inappropriate footwear are found to be the cause. Foot pain has reached up to 55.9% generally in the ones who are more engaged in walking and standing. Previous studies have shown that kinesio taping helps prevent injuries and reduce pain. Since footwear is only an interface between the ground and the foot, we combine kinesio taping with corrective footwear to see the impact. Our study aims to determine the combined effectiveness of kinesio taping and corrective footwear for ward nurses with foot pain. Through this study, we aim to see whether kinesio taping and corrective footwear help reduce pain for ward nurses with foot pain because nurses are at a higher risk as their profession demands more standing and walking. It was an experimental design study where subjects were randomly assigned into two groups- Group A (kinesio taping and corrective footwear) and Group- B (conventional exercise) for three weeks. The numerical Pain Rating Scale (NPRS) was used to measure pain score, Foot Function Index (FFI) to measure pain in terms of function and disability, the Navicular Drop Test (NDT) to measure pronation of the foot and wet test (an observational test) to see the arch of the foot - normal, flat or high arch. statistical analysis showed NPRS mean score for group A is 2.26 and for group B is 3.11, FFI score for group A is 13.00. Group B is 22.00. Both NPRS and FFI were highly significant (p<0.01). NDT is significant at a 1% probability level (p=.005< 0.01), as the mean score remained the same pre and post-treatment. All the interventions have brought about some improvement in each group post-treatment based on the mean score, but its significance varies. The intervention used in Group-A showed better results in alleviating pain. It is concluded that kinesio taping and corrective footwear were more effective in reducing pain among the nurses.